Eye Movements Reveal Optimal Strategies for Analogical Reasoning - Vendetti, Michael S.; Starr, Ariel; Johnson, Elizabeth L.; Modavi, Kiana; Bunge, Silvia A. (Frontiers in Psychology, 2017)
Analogical reasoning refers to the process of drawing inferences on the basis of the relational similarity between two domains. Although this complex cognitive ability has been the focus of inquiry for many years, most models rely on measures that cannot capture individuals’ thought processes moment by moment. In the present study, we used participants’ eye movements to investigate reasoning strategies in real time while solving visual propositional analogy problems (A:B::C:D). We included both a semantic and a perceptual lure on every trial to determine how these types of distracting information influence reasoning strategies. Participants spent more time fixating the analogy terms and the target relative to the other response choices, and made more saccades between the A and B items than between any other items. Participants’ eyes were initially drawn to perceptual lures when looking at response choices, but they nonetheless performed the task accurately. We used participants’ gaze sequences to classify each trial as representing one of three classic analogy problem solving strategies and related strategy usage to analogical reasoning performance. A project-first strategy, in which participants first extrapolate the relation between the AB pair and then generalize that relation for the C item, was both the most commonly used strategy as well as the optimal strategy for solving visual analogy problems. These findings provide new insight into the role of strategic processing in analogical problem solving.